Cover Image, Volume 6, Issue 4. (July 2017) - Tao, Hirotaka; Kawakami, Yasuhiko; Hui, Chi‐chung; Hopyan, Sevan
Abstract : The cover image, by Hirotaka Tao et al., is based on the Advanced Review The two domain hypothesis of limb prepattern and its relevance to congenital limb anomalies, DOI:10.1002/wdev.270 . Abstract : The cover image, by Hirotaka Tao et al., is based on the Advanced Review The two domain hypothesis of limb prepattern and its relevance to congenital limb anomalies, DOI:10.1002/wdev.270 .